Bio-physical properties of Norwegian coastal cod eggs - Jung, Kyung-Mi; Sundby, Svein; Thorsen, Anders; Folkvord, Arild; Kjesbu, Olav Sigurd (ICES, 2009)
Vertical distribution of fish eggs and larvae is a key factor for transport and retention of the offspring, and for problems linked to mixing/separation between populations, and hence for mechanism maintaining genetic differentiation among local populations, in combination with high site fidelity and natal homing of older cod. The vertical distribution is determined by the combined effects of local salinity structure of the ambient water and by the specific gravity of the eggs. The specific gravity of the eggs is determined their bio-physical characteristics. We have studied bio-physical properties of Norwegian Coastal cod (Gadus morhua) eggs from different areas (Porsangen, Tysfjord, and Helgeland).